Mining Risk Factors of Storm Surge Disasters Based on Disaster Prevention and Mitigation Policy Texts - Guo Tengjiao; Cao Qi; Ma Yufu; Yang Liejuan (Redai dili)
Disaster prevention and mitigation policy texts serve as a guidance and basis for the government to respond to disasters. They contain rich information on disaster risk factors, records the degree of damage caused by disaster hazard factors to disaster-bearing bodies, and provide disaster prevention measures. Risk factors form the foundation of a disaster risk assessment index. This study considered storm surges as an example and deconstructs risk factors into three dimensions-hazard, vulnerability, and disaster resistance capacity–by integrating disaster prevention and mitigation policy texts. Text mining techniques were used to analyze the composition and evolution characteristics of risk factors in policy contexts, with a focus on emphasizing disaster prevention and reduction at different stages. This study constructed a policy text-driven theoretical framework for disaster risk assessment, overcoming the limitations of traditional indicator systems that rely on statistical data and expert experience, and revealed the key role of institutional factors in risk formation. The results are as follows: (1) Policy texts can be used to extract a large number of storm surge risk factors, with hazard factors linked to high-frequency terms such as "sea level rise" and "typhoons," vulnerability to "coastal areas", "coastal zones", "land use", etc., and disaster resilience to "engineering defense," "financial support," etc. (2) There are significant differences in the focus on risk factors in policy texts at different stages. Before 2010, the focus was on identifying and monitoring disaster risks. From 2010-2015, the focus was on further refining the vulnerabilities of disaster-bearing bodies. After 2015, there was greater emphasis on the role of technological development in disaster resistance. These changes reflect the gradual deepening of policymakers' understanding of storm surge disaster risks. (3) The elements extracted from the policy text, such as "astronomical tide," "land reclamation," and "disaster insurance," have compensated for the neglect of human intervention and institutional factors in traditional indicator systems. This study pioneered a new paradigm of policy text analysis in disaster risk assessment at the methodological level, breaking through the traditional reliance on structured data in storm surge disaster risk assessments. Policy evolution analysis revealed changes in risk concerns.